Nitrogen Fertilizer Regulated Grain Storage Protein Synthesis and Reduced Chalkiness of Rice Under Actual Field Warming - Wang, Xueqin; Wang, Kailu; Yin, Tongyang; Zhao, Yufei; Liu, Wenzhe; Shen, Yingying; Ding, Yanfeng; Tang, She (Frontiers in Plant Science, 2021)
Our previous study has shown that nitrogen plays an important role in dealing with significant increased chalkiness caused by elevated temperature. However, the role of nitrogen metabolites has not been given sufficient attention and its regulatory mechanism is not clear. This study investigated the effects of high temperature and nitrogen fertilizer on the synthesis of grain storage protein, and further explored the quality formation mechanism under the actual scenario of field warming. Results showed increased temperature and nitrogen fertilizer could affect the activities of nitrogen metabolism enzyme GOGAT, GS and GPT, GOT and the expressions of storage protein synthesis factor genes GluA, GluB subfamily genes, pro14, and BiP1 and PDIL1, which co-induced the changes of storage protein synthesis in rice grains. Furthermore, increased temperature changed the balance of grain storage substances, and that may lead to the significantly increased chalky rate (197.67%) and chalkiness (532.92%). Moreover, there was a significant negative correlation between prolamin content and chalkiness, indicating that nitrogen fertilizer might regulate the formation of chalkiness by affecting the synthesis of prolamin. Results suggested nitrogen application could regulate the related core factors involved in nitrogen metabolism pathways, which in turn affects the changes in the storage protein components in the grain and further affects the quality formation. Therefore, as a conventional cultivation measure, nitrogen application would have certain application value in the future rice production in response to climate warming.